Breaking Barriers: An Innovative Tool to Assess the National and City-Level Physical Activity Policy Development to Practice Disconnect - Resendiz, Eugen; Ramírez-Varela, Andrea; Mejía-Grueso, Juliana; Moon, Jane; Mitáš, Josef; Brownson, Ross C; Salvo, Deborah; Pratt, Michael (Journal of physical activity & health, 2024)
BACKGROUND: Population-level physical activity increases are improbable without intersectoral collaboration across government levels and sectors to develop and implement physical activity promotion policies. This study aims to provide information about the development of the Interaction between National and Local Government Levels in Development and Implementation of Physical Activity Policies Tool (INTEGRATE PA-Pol). A framework was created to examine the development and implementation of national and subnational physical activity policies and the (mis)alignment between government levels. METHODS: The work was conducted in 3 phases: (1) a scoping review was carried out to identify local government physical activity promotion policies and instruments for assessing them, (2) an expert group designed 6 questionnaires, and (3) cognitive response testing was employed for validity testing and item modification with a panel of research and policy experts. RESULTS: The INTEGRATE PA-Pol Tool consists of 6 questionnaires assessing how national and subnational governments collaborate to develop and implement physical activity promotion policies. CONCLUSION: This tool can assist in better understanding the development and implementation of a public policy monitoring system that will allow for benchmarking and priority setting to comprehend how physical activity promotion policies are designed and executed.
Keywords: velkoměsta; Health Policy; průzkumy a dotazníky; lidé; zdravotní politika; podpora zdraví; Local Government; cvičení; Cities; místní státní správa; Exercise; Health Promotion; Surveys and Questionnaires; vytváření politiky; Policy Making; Humans